Role of natriuretic peptides in the assessment of aortic stenosis severity - Davičević Žaklina; Tavčiovski Dragan; Matunović Radomir; Vukotić Snježana; Mijailović Zdravko (Vojnosanitetski Pregled)
Background/Aim. Symptom onset is a critical point in natural course of aortic stenosis and the most important indication for aortic valve replacement. The aim of the study was to evaluate the role of natriuretic peptides level in the assessment of symtomatic status of patients with severe aortic stenosis and the preserved left ventricular systolic function. Methods. In 67 patients with isolated severe aortic stenosis symptomatic status, transthoracic echocardiography, and BNP and NT-proBNP plasma level were assesed. Natriuretic peptides levels were also measured in 36 healthy controls. Results. BNP and NT-proBNP levels were significantly higher in the patients with aortic stenosis compared with the healthy controls. The symptomatic patients had a higher level of natriuretic peptides than the asymptomatic ones (BNP 118 [29-266] vs 79 [44-90] pg/mL, p < 0.001; NT-proBNP 258 [67-520], vs 79 [77- 112] pmol/L, p < 0.0001). Natriuretic peptides levels increased with the severity of NYHA class. NT-proBNP level higher than 122 pmol/L was a cutoff value for detection of symptoms in the patients with severe aortic stenosis. Conclusion. The levels of natriuretic peptides were significantly higher in the patients with symptomatic aortic stenosis, and increased with NYHA class. Measurement of natriuretic peptides levels could be important addition to clinical and echocardiographic assessment in determing optimal timing for valve replacement in aortic stenosis.